Evolving spaces an exploratory study of house morphologies of mid-cost core houses in Davao City - Montealegre, Joash John G. (2023)
This study explored how households' changing needs in Davao City affect home qualities and layouts across family life cycle stages; namely the (1) Family Founding Stage, (2) Child-Bearing Stage, (3) Child-Rearing Stage, (4) Child-Launching Stage, and (5) Empty Nest Stage. By understanding preferences at each stage, the study identified space configurations reflecting evolving spatial needs. It employed a mixed method approach in analyzing 20 sample units in Davao City. Findings showed high satisfaction with homes at Empty Nest Stage due to its cumulative space alterations. Throughout the Family Founding Stage, occupants made minimal alterations to the house, as they were still adjusting to their new living situation. However, during the Child-Bearing Stage, gradual changes were observed to accommodate the needs of growing children, leading to the establishment of designated spaces for nurseries and play areas. The Child-Rearing Stage witnessed more substantial shifts in the house's morphology to meet the changing demands of parents and slightly older children, often involving the addition of spaces like a service kitchen and utility area. Subsequently, the Child-Launching Stage emphasized privacy and a more defined separation of access to social spaces. Finally, the Empty Nest Stage marked the completion of the family life cycle, with the current morphology serving as the baseline for future occupants. The house morphology changes with family life cycle, involving space expansion and adding amenities to meet evolving needs. Understanding these dynamics is vital for designing homes that adapt to changing family requirements.